Istisna-based product for project financing : a case study in Bank Islam Malaysia Berhad / Nurul Asyiqin Zakirah Anuar - Anuar, Nurul Asyiqin Zakirah (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
The evolution in the country of Malaysia especially in Islamic Banking and Finance called for a study to be made in regards with the Islamic Financial Institutions’ services and product in order to be in line with the development progression. Istisnabased product for project financing in Bank Islam Malaysia Berhad has been chosen as the subject of study. This study intends to find out the application, effectiveness and challenges related to the product known as “Project Financing/Bridging (Istisna’) in BIMB from the year of 2014 up to 2017. The product of the contract of istisna’ is in the interest of this study as it is an ideal option in financing any infrastructure project aside from the other financing tools like bay’ bithaman ‘ajil, murabaha, ijara, salam, mudaraba, musharaka and sukuk. This study is also conducted to raise public awareness regarding the product to stimulate and enhance the application as well as the utilization of the product in project financing.